Electric myographic control of electric therapeutic apparatus -ceragem master cgm 3500 influence on backbone of patients with scoliosis - M. V. Kupreenko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of effectiveness of electric therapeutic apparatus Ceragem master CGM 3500 in its influence on backbone of patients with scoliosis. Material: in examination 11 female patients with scoliosis of age from 21 to 35 years and 12 practically healthy persons participated. The research of para-vertebral muscles of back was fulfilled with method of electric myography. Results: we determined positive effect in nervous-muscular functioning of back. The proof was increase of integrated amplitude of back muscles' electric activity on convex and concave sides of scolytinae arc; increase of maximal amplitude of H-reflex and M-response. Conclusions: standard electric myography permits to receive objective information about functional state of muscles of patients with scoliosis and assess effectiveness of rehabilitation process with application of electric therapeutic apparatus - - Ceragem Master CGM 3500.